The Role of Quality Control and Total Quality Management in Maintaining the Reputation of Higer Education Institutions in the Global Era - Hamidah Darma; Fitriana Pohan; Irsan Rangkuti; Selamat Triono; Tengku Teviana (Edumaspul: Jurnal Pendidikan, 2023)
In the context of education, higher education institutions must be able to implement a good quality hierarchy mechanism so that the institution can provide the expected quality and always strive to improve the quality it has achieved in maintaining its reputation. The right strategy is needed so that higher education institutions can systematically become quality and reputable institutions. Improving the quality of institutions runs continuously so that public participation and expectations of managed educational institutions become stronger and able to maintain their reputation. Quality control and total quality management are methods to provide assurance to the public of the quality and reputation of education organized by institutions. Quality control and total quality management are methods to provide assurance to the public of the quality and reputation of education organized by institutions. Continuously improvement activity is proof of sincerity in presenting quality Higher Education institutions through quality control and total quality management.